A proposed teaching guide for our national heritage and identity and our changing social institutions - Belonio, Nelson Paderna 1945- (1979)
This research paper proposed a Teaching Guide for two learning units in Social Studies II: "Our National Heritage and Identity" and "Our Changing Social Institutions". A conceptual-chronological approach was used in this study. This teaching guide observes the conceptual-chronological approach in teaching history. It emphasized selection and development of concepts, making generalization and chronological arrangement of content. The foregoing facts served as the guiding posts in conceiving and providing the teaching-learning processes contained in the teaching guide which are all designed to ensure the goals of the New Social Studies Curriculum for the learner.
Vita.
Thesis (M.A. Social Studies Education)--University of the Philippines, Diliman.
Keywords: Social sciences -- Study and teaching (Secondary) -- Philippines; Teaching -- Philippines -- Aids and devices; Philippines -- History -- Study and teaching (Secondary).